Mitochondrial and Sarcoplasmic Reticulum Interconnection in Cardiac Arrhythmia - Salazar-Ramírez, Felipe; Ramos-Mondragón, Roberto; García-Rivas, Gerardo (Frontiers in Cell and Developmental Biology, 2021)
Ca2+ plays a pivotal role in mitochondrial energy production, contraction, and apoptosis. Mitochondrial Ca2+-targeted fluorescent probes have demonstrated that mitochondria Ca2+ transients are synchronized with Ca2+ fluxes occurring in the sarcoplasmic reticulum (SR). The presence of specialized proteins tethering SR to mitochondria ensures the local Ca2+ flux between these organelles. Furthermore, communication between SR and mitochondria impacts their functionality in a bidirectional manner. Mitochondrial Ca2+uptake through the mitochondrial Ca2+uniplex is essential for ATP production and controlled reactive oxygen species levels for proper cellular signaling. Conversely, mitochondrial ATP ensures the proper functioning of SR Ca2+-handling proteins, which ensures that mitochondria receive an adequate supply of Ca2+. Recent evidence suggests that altered SR Ca2+proteins, such as ryanodine receptors and the sarco/endoplasmic reticulum Ca2+ ATPase pump, play an important role in maintaining proper cardiac membrane excitability, which may be initiated and potentiated when mitochondria are dysfunctional. This recognized mitochondrial role offers the opportunity to develop new therapeutic approaches aimed at preventing cardiac arrhythmias in cardiac disease.